Doughnut Economics: Guiding Visionary Youth Towards Sustainability - Anisatul Maghfiroh (Journal of Business Improvement, 2025)
The convergence of economics and ecology is increasingly recognized as crucial in addressing global sustainability challenges. This paper conducts a comprehensive literature review to explore the role of Doughnut Economics as an innovative framework that could guide a new generation of visionary youth. The review analyzes existing studies on Doughnut Economics, focusing on its impact on sustainable development, educational integration, and youth engagement. The findings indicate that Doughnut Economics provides a robust conceptual foundation that aligns with the aspirations of young people, offering them a clear roadmap to contribute to a more just and sustainable world. Furthermore, the paper identifies key strategies for embedding Doughnut Economics into educational curricula and public policy, ensuring its principles are widely adopted and implemented across generations